NAR DAN NUR PADA QS. AL-BAQARAH AYAT 17-18 ANALISIS SEMIOTIK TRICHOTOMY RELATIONS PIERC - Citra Dewi Mahajani (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2026)
This study examines the meaning of the words nar and nur in QS. al-Baqarah verses 17-18 through the semiotic trichotomy relations approach developed by Charles Sanders Peirce. The verse depicts the parable of the condition of the hypocrites through the symbols of light and fire which initially provide illumination, but then go out so that they return to darkness. This study uses a qualitative method with a type of library research and semiotic analysis that highlights the relationship of signs in the form of representamen, objects, and interpretants rooted in icons, indices, and symbols. The results of the study show that the words nar and nur not only have a literal meaning as fire and light, but also function as symbols of guidance and guidance from Allah. In the context of the verse, light is interpreted as guidance that initially illuminated the hypocrites, but was later revoked because they did not use it properly so that they are depicted as losing their light and getting lost in darkness.